American Religious Responses to Kristallnacht - Mazzenga, M. author. aut Link
V, 215 p.
Keywords: This book examines how American Protestants, Catholics and Jews responded to the persecution of Jews in Germany and German-occupied territory in the 1930s. The essays focus on American religious responses to Kristallnacht and represent the first examination of multi-religious group responses to the beginnings of the Holocaust.